Healthcare access for children in a low-income area in Cape Town: A mixed-methods case study - Luke B. Profitt; Graham Bresick; Liezel Rossouw; Ben Van Stormbroek; Tasleem Ras; Klaus Von Pressentin (South African Family Practice)
Background: In Cape Town, the under-5 mortality rate has plateaued to 20 per 1000 live births, with 60% of child deaths occurring out of hospital. The southern subdistrict has the largest paediatric population in Metro West and accounts for 31% of deaths. This study aimed to uncover the access barriers and facilitators underlying this high burden of out-of-hospital deaths.